E-022 The Surpass™ IntraCranial Aneurysm Embolization System Pivotal Trial to treat large OR giant wide neck aneurysms (SCENT Trial). (29th July 2016) - Kan, P; Meyers, P; Hanel, R
Abstract : Introduction: Stroke is the fourth leading cause of death in the United States and the most common life-threatening neurological disease. 1 Hemorrhagic stroke occurs in 13% of stroke patients with the majority of these events being related to the rupture of intracranial aneurysms. 2 As many as 6% of the general population may have an unruptured intracranial aneurysm which, if left untreated, may lead to a neurological event or death. The Surpass™ Flow Diverter was developed to treat aneurysms not amenable to surgical or current standard endovascular treatment. Materials and methods: The Surpass™ Flow Diverter System is comprised of the Surpass™ Flow Diverter, the Surpass Delivery Catheter and Pusher, a second microcatheter that resides within the delivery catheter. The Surpass™ Flow Diverter is preloaded on the delivery catheter and is available in diameters ranging from 3 to 5 mm and lengths of 15 to 50 mm. The SCENT Trial is an international, multi-center, prospective, non-randomized trial comparing the outcomes of Surpass™ Flow Diverter treatment to a historical control. It is designed to evaluate the safety and efficacy of the Surpass™ Flow Diverter in the treatment of large or giant wide neck intracranial aneurysms. Subjects between the ages of 19 to 80 years having a single targeted intracranial aneurysm that is located in the internal carotid artery (ICA) distribution up to the terminus with a neck ≥4 mm or no discernible neck and an aneurysm size ≥10 mm (including saccular, fusiform, and dissecting aneurysms) are eligible for participation in the study. The primary safety endpoint is the percent of subjects experiencing neurologic death or major ipsilateral stroke through 12 months. The primary effectiveness endpoint is the percent of subjects with 100% occlusion (Raymond Class 1) without clinically significant stenosis (defined as ≤50% stenosis) of the parent artery and any subsequent treatment of the target aneurysm at 12 months. Results and Conclusion: The enrollment of 180 subjects in the SCENT trial was completed on November 30, 2015. Up to 30 sites were targeted for participation in the study. All 12 month primary-endpoint follow-up visits are expected to be completed in November 2016. Disclosures: P. Kan: 2; C; Stryker Neurovascular, Medtronic. P. Meyers: None. R. Hanel: 2; C; Stryker Neurovascular, Covidien, Codman Neuro, MicroVention. 4; C; Blockade.